Students’ comparative perception toward the use of Google Translate and ChatGPT in translation task - Manindar, Maharida; Saleh, Noerjihad; Abbas, Herawaty; Kamsinah; Rahman, Patur (Journal of Islamic, Social, Economics and Development, 2025)
This study focuses on comparing students’ perceptions of using Google Translate and ChatGPT as translation tools. As neural machine translation (NMT) continues to develop, understanding how students evaluate these technologies in terms of accuracy, usability, and reliability is essential for language learning and translation pedagogy. Employing a quantitative approach, this research collected data through Likert scale questionnaires from 30 university students at two different institutions: Unismuh Makassar and UIN Alauddin Makassar. Descriptive statistics and independent samples T-tests were used to analyze the students’ perception of using both of the tools and its trend differences based on comparing two institutions. The findings indicate that both tools are widely used and positively perceived, though students noted differences in familiarity, accuracy, language style, contextual understanding, and user-friendliness. Nevertheless, the statistical analysis showed no significant difference in overall perception scores between the two campuses, where Unismuh and UIN Alauddin Makassar indicated similar trends. These results suggest that while both Google Translate and ChatGPT serve as helpful translation aids, students’ preferences are influenced by specific features and individual user experiences. The study highlights the importance of integrating digital translation tools thoughtfully into translation education.